Adaptins: The Final Recount - Boehm, Markus (The American Society for Cell Biology, 2001)
Adaptins are subunits of adaptor protein (AP) complexes involved in the formation of intracellular transport vesicles and in the selection of cargo for incorporation into the vesicles. In this article, we report the results of a survey for adaptins from sequenced genomes including those of man, mouse, the fruit fly Drosophila melanogaster, the nematode Caenorhabditis elegans, the plant Arabidopsis thaliana, and the yeasts, Saccharomyces cerevisiae and Schizosaccharomyces pombe. We find that humans, mice, and Arabidopsis thaliana have four AP complexes (AP-1, AP-2, AP-3, and AP-4), whereas D. melanogaster, C. elegans, S. cerevisiae, and S. pombe have only three (AP-1, AP-2, and AP-3). Additional diversification of AP complexes arises from the existence of adaptin isoforms encoded by distinct genes or resulting from alternative splicing of mRNAs. We complete the assignment of adaptins to AP complexes and provide information on the chromosomal localization, exon-intron structure, and pseudogenes for the different adaptins. In addition, we discuss the structural and evolutionary relationships of the adaptins and the genetic analyses of their function. Finally, we extend our survey to adaptin-related proteins such as the GGAs and stonins, which contain domains homologous to the adaptins.